Nucleosome assembly on the human c-fos promoter interferes with transcription factor binding. - Schild-Poulter, C (1996)
cAMP-responsive-element (CRE)-binding factors interaction with nucleosomal DNA has been investigated in vitro on the human c-fos promoter. Analysis of nucleosome reconstitution of this promoter shows a preferential nucleosome positioning on the proximal promoter sequences, including the CRE centered at -60 relative to the start site of transcription. CRE-binding protein (CREB) and modulator protein (CREM) are unable to interact with their recognition site incorporated in a nucleosome. However, competition between transcription factor binding and nucleosome assembly allows CREM binding and induces important modifications in the nucleosomal structure suggesting the displacement of nucleosomes. These findings imply that binding of transcription factors to the CRE prior to cAMP induction might be required to prevent the incorporation of this element in a nucleosome.